Resonant Absorption and Fluctuations via Hybrid Simulations on Coronal Loops. I. Plasma Multifluid Description - Hugo A. Carril; Jaume Terradas; Roberto E. Navarro; Adolfo F. Viñas; Marcel Goossens (The Astrophysical Journal)
We investigate the resonant absorption process of a combination of left- and right-hand polarized waves (with a fixed perturbation amplitude) in a plasma slab with linearly inhomogeneous particle densities. Different thicknesses of the layers and angles of the background magnetic field to the plane of the slab, representing the degree of magnetization of the slab, are studied via 2D−3V PIC-hybrid simulations with a fixed perturbation amplitude. We identify the process of resonant absorption of the large-scale mode in the inhomogeneous layers and compare the damping rate of the transverse oscillations with single-fluid, linear MHD estimations. By following the spectral densities of the magnetic field fluctuations, it is found that kinetic scales are achieved in most of the simulated cases, particularly in the case of thinner inhomogeneous layers and in cases where the plasma slab is not weakly magnetized. In particular, the scales of the fluctuations can reach the proton inertial length. The small-scale fluctuations are identified as quasi-perpendicular oscillations localized within the inhomogeneous layers, and their properties in the spectral representation agree with theoretical properties of kinetic Alfvén waves predicted by kinetic and Hall-MHD theories.